Comparative Diversity of Non-Volant Small Mammals in Hutan Lagenda and Waterfall Gunung Ledang - Ng, Yi Thong; Sapaat, Arney (Enhanced Knowledge in Sciences and Technology, 2025)
Gunung Ledang is a biodiversity hotspot of Johor, Malaysia. This forest includes a variety of habitats that support a broad spectrum of species, including small mammals that support the stability of ecosystems. This study investigates and compares the diversity of non-volant small mammals in two distinct sites within Gunung Ledang Johor National Park, Hutan Lagenda and Waterfall as there is not much data on the species diversity in Gunung Ledang National Park. At each location, 24 cage traps were deployed with bananas, dead fish and belacan as bait. A total of 8 individuals were captured from seven species and were classified into three families during twelve days of sampling at both locations. The Muridae family was the most abundant species found with Leopoldamys sabanus (n=1), Maxomys rajah (n=1), Rattus tiomanicus (n=1), and Rattus norvegicus (n=1). The second most abundant species was the Sciuridae family with Callosciurus notatus (n=1) and Sundasciurus tenuis (n=1) and the last was Tupaiidae, with one species recorded, Tupaia glis (n=1). The Waterfall site recorded five species whereas Hutan Lagenda reported two species, indicating a higher species richness in the Waterfall site. The p-value of 0.10 showed that the two locations were not significantly different as both of the sites might share similar habitat characteristics and ecological niches.